1950
DOI: 10.1055/s-0028-1117805
|View full text |Cite
|
Sign up to set email alerts
|

Die Kobalttherapie

Abstract: Die Spurenelementforschung der jüngsten Vergangenheit hat ein bisher wenig beachtetes Element in den Vordergrund treten lassen, das Metall Kobalt. Sein Vorkommen im Belebten ist zwar schon lange bekannt, seine Wirkung an Tier und Mensch erst in den letzten Jahren genauer untersucht. Das hiiufigere Auftreten

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

1967
1967
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 0 publications
0
21
0
1
Order By: Relevance
“…Though cobalt is often effective in raising the haemoglobin, its mode of action is not known, but it may act by causing direct anoxia of the bone-marrow cells by enzyme inhibition (Weissbecker, 1950). Gardner (1953) and Kriss et al (1955) reported certain sideeffects after administration of cobalt even for short periods.…”
Section: Discussionmentioning
confidence: 99%
“…Though cobalt is often effective in raising the haemoglobin, its mode of action is not known, but it may act by causing direct anoxia of the bone-marrow cells by enzyme inhibition (Weissbecker, 1950). Gardner (1953) and Kriss et al (1955) reported certain sideeffects after administration of cobalt even for short periods.…”
Section: Discussionmentioning
confidence: 99%
“…Neurological, renal, and cardiovascular changes occurring after the administration of cobalt and certain of its salts to man and animals have been reported (Weissbecker, 1950;Gardner, 1953;Holly, 1955;Kriss, et al, 1955;De Moraes and Mariano, 1967;Schirrmacher, 1967;Hall and Smith, 1968;Schroeder and Nason, 1969). Because of the histological findings and clinical reports it was thought that a long-term study of the distribution and route of excretion of the wear products in patients with T.H.Rzs was required.…”
Section: Introductionmentioning
confidence: 98%
“…[7] Cobalt acts by stabilizing a factor known as hypoxia inducible factor 1α (HIF1α). [8] While effective in the treatment of anaemia, chronic administration of cobalt, presumably due to deposition of cobalt in tissues and organs, has been associated with a number of toxic effects, which has limited its use as a therapeutic agent. Under normoxic conditions, HIF1α is rapidly degraded.…”
Section: Introductionmentioning
confidence: 99%